Enhancing Fine Motor Skills in Early Childhood Through Fun Cooking Activities: A Quasi-Experimental Study in Purwakarta, Indonesia - Maranatha, Jojor Renta; Briliany, Noviarta (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2023)
This quasi-experimental study investigates the impact of engaging in cooking activities on fine motor skill development in kindergarten children aged 4-5 in Purwakarta, Jawa Barat, Indonesia. Adopting a Nonequivalent Control Group Design, the research compared two groups: an experimental group participating in fun cooking activities and a control group following traditional teaching methods. Pretest and posttest assessments were conducted using a rating scale-based observation tool to measure fine motor skills. The intervention comprised three sessions of cooking activities, focusing on enhancing fine motor abilities. Data analysis utilized the N-Gain score method to quantify skill improvements. Results revealed a medium N-Gain score in the experimental group, indicating a significant enhancement in fine motor skills due to the cooking activities. In contrast, the control group showed no significant change. These findings suggest that fun cooking activities effectively develop fine motor skills in early childhood, offering a practical and engaging alternative to conventional teaching methods. This study's implications extend to curriculum design in early childhood education, advocating for integrating diverse and interactive activities. However, its limited geographical scope and the short duration of the intervention point to the need for further research. Future studies should explore long-term effects and broader applicability, potentially impacting policies and practices in early childhood education. This research adds to the growing body of literature that supports innovative and engaging learning approaches in the foundational years of schooling.